2021
DOI: 10.1142/s0218348x21400028
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Fly Ash, Pva Fiber, Mgo and Shrinkage-Reducing Admixture on the Frost Resistance of Face Slab Concrete via Pore Structural and Fractal Analysis

Abstract: Face slab concrete suffers from serious frost damage in cold regions in China, how to improve the frost resistance of face slab concrete in cold regions is one of the important issues in concrete faced rockfill dam (CFRD) design and construction. The results in this paper indicate that the frost resistance of concrete can be improved by adding fly ash, fiber, MgO and shrinkage-reducing admixtures (SRA), and the efficiency is in the sequence: (fly ash + fiber) > fiber > fly ash > MgO > SRA. The incorporation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
84
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(88 citation statements)
references
References 55 publications
4
84
0
Order By: Relevance
“…It is consistent with the results of this paper. Tong (Tong, 2018) also pointed out that SAP has a negative effect on the flexural strength of concrete or mortar. This can be attributed to the following facts: firstly, all the strength of SAP concrete decreases with the increase of SAP and internal curing water, which increasing the total watercement ratio.…”
Section: Strength Variation With Sap Contentmentioning
confidence: 99%
See 2 more Smart Citations
“…It is consistent with the results of this paper. Tong (Tong, 2018) also pointed out that SAP has a negative effect on the flexural strength of concrete or mortar. This can be attributed to the following facts: firstly, all the strength of SAP concrete decreases with the increase of SAP and internal curing water, which increasing the total watercement ratio.…”
Section: Strength Variation With Sap Contentmentioning
confidence: 99%
“…According to RILEM (Mechtcherine et al, 2014), when SAP releases internal curing water, it shrinks and leaves air voids behind, which act as weak spots in the material structure, decreasing the flexural strength. Tong (2018) pointed out that the existence of pores due to the shrinkage of SAP is a kind of defect in the concrete.…”
Section: Strength Variation With Sap Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…The above MIP results could be used to characterize the porosity distribution and evolution of tuff powder-cement paste, but fail to characterize the complexity of the internal pore structure. For this purpose, the relevant literature applies the fractal theory to analyze the pore structure of cement-based materials (Wang et al, 2020a;Wang et al, 2020b). The fractal dimension of the pore surface (Ds) is introduced to quantitatively characterize the surface characteristics of the irregular pore structure of tuff powder-cement paste.…”
Section: Fractal Dimension Of Pore Surface Areamentioning
confidence: 99%
“…The fractal dimension of the pore surface (Ds) is introduced to quantitatively characterize the surface characteristics of the irregular pore structure of tuff powder-cement paste. Studies have (Wang et al, 2020a;Wang et al, 2020b;Wang et al, 2020c;Rahman, 1997) shown that the surface fractal dimension value is primarily related to the pore distribution characteristics. The Ds is within the range of 2-3.…”
Section: Fractal Dimension Of Pore Surface Areamentioning
confidence: 99%